2021
DOI: 10.3389/fnmol.2021.656740
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and Copper Brain Levels and Expression of Neurotransmitter Receptors in Two Rat ASD Models

Abstract: Zinc and copper are important trace elements necessary for the proper functioning of neurons. Impaired zinc and/or copper metabolism and signaling are implicated in many brain diseases, including autism (ASD). In our studies, autistic-like behavior in rat offsprings was induced by application to pregnant mothers valproic acid or thalidomide. Zinc and copper contents were measured in serum and brain structures: hippocampus, cerebral cortex, and cerebellum. Our research shows no interconnections in the particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…The dorsal and median raphe nuclei may differ in vulnerabilities to VPA treatments. Reduced serotonin receptors have also been found in the hippocampus [93]. In other brain regions, alterations in 5-HT levels are more consistent.…”
Section: Abnormalities Of Serotonergic Systems In Vpa-induced Asd Modelsmentioning
confidence: 80%
See 2 more Smart Citations
“…The dorsal and median raphe nuclei may differ in vulnerabilities to VPA treatments. Reduced serotonin receptors have also been found in the hippocampus [93]. In other brain regions, alterations in 5-HT levels are more consistent.…”
Section: Abnormalities Of Serotonergic Systems In Vpa-induced Asd Modelsmentioning
confidence: 80%
“…At the behavioral level, consistent behavioral phenotypes have been found along with catecholaminergic abnormalities in VPA-treated rodents, including reduced social behaviors, increased repetitive, depressive and anxious behaviors, and impaired memory [14,66,84,86,93,99,131,133,134,138]. Impaired cognitive flexibility and temporal processing have also been observed in VPA-treated rodents, implicating abnormal functions of the prefrontal cortex [131,132].…”
Section: Behavioral Phenotypes Related To Altered Catecholamine Syste...mentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, studies have revealed different Cu content in different regions of the brain. 15,16 This is important because the hippocampus and cortex, for example, are more susceptible to plaque formation. 17 Copper quantitation in biological samples is commonly accomplished by separations and spectroscopic techniques with high sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have revealed different Cu content in different regions of the brain. 15,16 This is important because the hippocampus and cortex, for example, are more susceptible to plaque formation. 17…”
Section: Introductionmentioning
confidence: 99%